Creativity as a platform for sustainable development in the economic periphery: The case of Masbate City, the Philippines - Asilum, Jofer B. (Diliman Review, 2024)
Creativity is integral in sustainable urban development. However, its effective use as a development platform is particularly challenging for the economic peripheries. Applying the Sustainable Livelihoods Framework, this study explores the sustainability of creative activities as a development platform in Masbate City, a periphery city in the Philippines. Using qualitative data from focus group discussions with three local creative groups, this study finds that Masbate City’s cultural festivals and the national programs for arts education were integral in the participants’ involvement in creative activities. By utilizing creative activities as a livelihood, the participants either enabled or improved their access to financial capital, which became their avenue to also enable or improve their access to other livelihood capitals. These contributed in improving their wealth and poverty situation, well-being, capabilities, and employment options, were crucial in adapting to external shocks. However, sustaining Masbate City’s creative economy is hindered by its local government’s weak capacity in supporting the creative workers’ needs and in creating stable markets for their products. Thus, to make creativity a sustainable development platform in Masbate City, this study recommends building its institutional capacity in creative economy management, and developing its creative economy infrastructure, labor force and markets.